In vivo synaptic transmission and morphology in mouse models of Tuberous sclerosis, Fragile X syndrome, Neurofibromatosis type 1, and Costello syndrome - Wang, Tiantian; de Kok, Laura; Willemsen, Rob; Elgersma, Ype; Borst, J. Gerard G. (Frontiers in Cellular Neuroscience, 2015)
Defects in the rat sarcoma viral oncogene homolog (Ras)/extracellular-signal-regulated kinase and the phosphatidylinositol 3-kinase-mammalian target of rapamycin (mTOR) signaling pathways are responsible for several neurodevelopmental disorders. These disorders are an important cause for intellectual disability; additional manifestations include autism spectrum disorder, seizures, and brain malformations. Changes in synaptic function are thought to underlie the neurological conditions associated with these syndromes. We therefore studied morphology and in vivo synaptic transmission of the calyx of Held synapse, a relay synapse in the medial nucleus of the trapezoid body (MNTB) of the auditory brainstem, in mouse models of tuberous sclerosis complex (TSC), Fragile X syndrome (FXS), Neurofibromatosis type 1 (NF1), and Costello syndrome. Calyces from both Tsc1+/- and from Fmr1 knock-out (KO) mice showed increased volume and surface area compared to wild-type (WT) controls. In addition, in Fmr1 KO animals a larger fraction of calyces showed complex morphology. In MNTB principal neurons of Nf1+/- mice the average delay between EPSPs and APs was slightly smaller compared to WT controls, which could indicate an increased excitability. Otherwise, no obvious changes in synaptic transmission, or short-term plasticity were observed during juxtacellular recordings in any of the four lines. Our results in these four mutants thus indicate that abnormalities of mTOR or Ras signaling do not necessarily result in changes in in vivo synaptic transmission.